Academic Performance of Graduate Students in Video-Conference-Assisted Online Learning during COVID-19 Based on Cohort Data in Pakistan and Indonesia - M Bhatti, Faqir; Miranda, Eka (Indonesian Journal of Mathematics Education, 2024)
The current study found that the COVID-19 pandemic isolation impacted the academic performance of most participants with varied degrees and graduate students in Computer Science and Math. With the option of self-study, online education keeps students on track. This paper aimed to investigate the academic performance impact of graduate program students in the fields of computer science, math, and information systems on online learning during the COVID-19 pandemic. A total of 89 responses were retrieved. The 71 (79.78%) responses came from students at an university in Raiwind, Lahore, Pakistan, and the 18 (20.22%) responses came from students at an university in Jakarta, Indonesia. We discovered that the essential issue of online education was providing students and instructors with easy access to interactive study materials such as video learning. Another significant challenge was the availability of an internet connection, as online learning depended on it. During the COVID-19 pandemic, most students get high course grades (35.96%) and maintain steady course grades (29.21%) in online learning, with some even achieving very good course grades (17.98%). Only a few students (12.36%) and very few (4.49%) received lower grades.